You’re so good-looking and wise, my powerful leaders! When deference becomes flattery in employee-authority relations - De Clercq, D.; Pereira, R. (Personnel Review, 2022)
Purpose – The purpose of this study is to investigate the relationship between employees’ deference to leaders’ authority and their upward ingratiatory behavior, which may be invigorated by two personal resources (dispositional greed and social cynicism) and two organizational resources (informational justice and forgiveness climate). Design/methodology/approach – In this study survey data were collected among employees who work in the banking sector. Findings – Strict adherence to leaders’ authority stimulates upward ingratiatory behavior, especially when employees (1) have a natural tendency to want more, (2) are cynical about people in power, (3) believe they have access to pertinent organizational information and (4) perceive their organization as forgiving of mistakes. Practical implications – For human resource (HR) managers, this study points to the risk that employees’ willingness to comply blindly with the wishes of organizational leaders can escalate into excessive, inefficient levels of flattery. Several personal and organizational conditions make this risk particularly likely to materialize. Originality/value – This study extends prior human resource management (HRM) research by revealing the conditional effects of an unexplored determinant of upward ingratiatory behavior, namely, an individual desire to obey organizational authorities unconditionally.